2020
DOI: 10.3906/sag-1910-13
|View full text |Cite
|
Sign up to set email alerts
|

Validity and reliability study of the Turkish version of the self-efficacy for managing chronic disease 6-item scale

Abstract: Background/aim: The measurement of self-efficacy is an important step toward improving chronic disease management, enhancing adherence to treatment, and assessing patients with chronic diseases. The purpose of this study was to assess the validity and reliability of the Turkish version of the Self-Efficacy for Managing Chronic Disease 6-Item Scale. Materials and methods: In this methodological study, the sample consisted of 211 patients receiving chronic disease care in 2 family health centers in İstanbul, Tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 23 publications
(60 reference statements)
0
17
0
2
Order By: Relevance
“…SEMCD consists of 10 sub-dimensions on a 10-point Likert-type scale “1” being the “not at all confident” and “10” being the “totally confident.” The higher score indicates increase management in self-efficacy about their chronic disease. The 6-item version was adapted to the Turkish language and culture by Incirkuş and Nahcivan (2020) . According to this study, they indicated the Cronbach alpha values for the reliability as 0.95 for the SEMCD-total score and reported that it is a reliable and valid tool for clinical practice among Turkish patients.…”
Section: Methodsmentioning
confidence: 99%
“…SEMCD consists of 10 sub-dimensions on a 10-point Likert-type scale “1” being the “not at all confident” and “10” being the “totally confident.” The higher score indicates increase management in self-efficacy about their chronic disease. The 6-item version was adapted to the Turkish language and culture by Incirkuş and Nahcivan (2020) . According to this study, they indicated the Cronbach alpha values for the reliability as 0.95 for the SEMCD-total score and reported that it is a reliable and valid tool for clinical practice among Turkish patients.…”
Section: Methodsmentioning
confidence: 99%
“…Self-efficacy means an individual’s confidence in their own problem solving and task completion ability ( Sun and Chen, 2016 ; Ghazi et al, 2018 ). İncirkus and Nahcivan (2020) observe that self-efficacy refers to people’s belief in their ability to implement an action plan, deal with challenges, and make the judgments that make a particular action successful. Mamaril et al (2016) and Liu et al (2020) indicated that self-efficacy is an individual’s conjecture and judgment of whether they have the ability to complete a certain behavior, which can reflect the individual’s belief in taking appropriate action to address environmental challenges.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…However, since self-efficacy is a kind of behavioral cognition, a psychological scale to measure personal self-efficacy is needed. A number of different self-efficacy scales have been developed for various fields, such as self-efficacy in the medical field ( Lorig et al, 1989 ; İncirkus and Nahcivan, 2020 ), general self-efficacy scales in the workplace ( Chen et al, 2004 ), self-efficacy scale for engineering education ( Mamaril et al, 2016 ), multi-dimensional self-efficacy scale for adolescents ( Bandura, 1990 ), teacher research self-efficacy scale ( Wester et al, 2019 ), teacher self-efficacy scale for student-oriented teaching ( Kilday et al, 2016 ), college student self-efficacy scale ( Khasawneh et al, 2009 ), and a mathematical self-efficacy energy scale ( Betz and Hackett, 1983 ). Based on the development of education in the high-tech era, the popularization of technology-assisted teaching has led many researchers to study the role of self-efficacy when the Internet or technology is applied to teaching, and develop numerous Internet and technology-related self-efficacy scales, such as the Internet self-efficacy scale ( Hsu and Chiu, 2004 ; Kao et al, 2011 ), the computer ethical self-efficacy scale ( Kuo and Hsu, 2001 ), and the Internet ethical self-efficacy scale ( Williamson et al, 2011 ).…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…Öz yeterliliğin değerlendirilmesi için geliştirilen ölçek çalışmalarından bazıları kronik hastalık yönetimi, günlük yaşam aktivitelerinin yönetimi, tedavi yönetimi, semptom yönetimi, belirli bir hastalığın yönetimi gibi konuları ele almaktadır (16)(17)(18)(19)(20)(21)(22)(23). Ülkemizde geçerlik güvenirlik aşamalarına uygun şekilde yapılan çalışmalarla bu ölçeklerden bazıları Türkçe literatüre kazandırılmıştır (24)(25)(26)(27)(28)(29).…”
unclassified